Targeting Trop2 in solid tumors: a look into structures and novel epitopes - Liu, Xinlin; Li, Jiyixuan; Deng, Junwen; Zhao, Jianan; Zhao, Gaoxiang; Zhang, Tingting; Jiang, Hongfei; Liang, Bing; Xing, Dongming; Wang, Jie (Frontiers in Immunology, 2023)
Trophoblast cell surface antigen 2 (Trop2) exhibits limited expression in normal tissues but is over-expressed across various solid tumors. The effectiveness of anti-Trop2 antibody-drug conjugate (ADC) in managing breast cancer validates Trop2 as a promising therapeutic target for cancer treatment. However, excessive toxicity and a low response rate of ADCs pose ongoing challenges. Safer and more effective strategies should be developed for Trop2-positive cancers.The dynamic structural attributes and the oligomeric assembly of Trop2 present formidable obstacles to the progression of innovative targeted therapeutics. In this review, we summarize recent advancements in understanding Trop2's structure and provide an overview of the epitope characteristics of Trop2-targeted agents. Furthermore, we discuss the correlation between anti-Trop2 agents' epitopes and their respective functions, particularly emphasizing their efficacy and specificity in targeted therapies.